REATOR DE LEITO EMPACOTADO EM ESCALA PILOTO PARA REMOÇÃO DE MATÉRIA ORGÂNICA E NITROGENADA DE ESGOTO SANITÁRIO - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The main objective of this research was to evaluate the performance of a pilot scale reactor of packed bed and continuous flow, on different aeration operating conditions, in the biological removal of carbonaceous and nitrogenous matter from sanitary effluent. The reactor has a total volume of 5.65 m³, and a useful volume of 4.75 m³ due to the volume occupied by the structured bed. The medium used to fix microorganisms was the device called Biobob®, which consists of a polyurethane foam matrix enveloped by a polypropylene structure, with a cylindrical geometry of 45 mm in diameter and 60 mm in height. The reactor was operated with a 12 hour Hydraulic Retention Time (HRT), recirculation rate of 2 times feed rate and was continuously fed by a mixture of untreated sewage and effluent from an Upflow Anaerobic Sludge Blanket (UASB) in the proportion of 1:1 (v:v). Three 180-minute cycles of operation were performed: (1) continuous aeration for 180 minutes, (2) aeration 60 minutes and no aeration for 120 minutes and (3) aeration for 120 minutes and no aeration for 60 minutes. The results showed that there was no statistical difference in the efficiency of Chemical Oxygen Demand (COD) reductions between the three conditions studied, with mean efficiencies of 76.34%, 75.32% and 79.80%, respectively, indicating that the aeration did not influence the reduction efficiency. The COD concentrations effluent from the reactor varied between 31 mg.L-1 and 206 mg.L-1. The efficiency of nitrification was shown to be a limiting factor in NT removal. The conditions (1) and (3) with higher nitrification rates, 75% and 70%, respectively, obtained the best NT removal efficiencies, with rates of 65% in both. The COD / NTK ratio presented a high average during the 3 stages of the research, with an observed value of 9.59. Denitrification showed mean removals of 87% (1), 89% (2) and 94% (3). Condition (3) presented a statistically significant difference with the others due to the greater availability of electron donors, with a COD/NTK ratio of 11.2. From the results, we can conclude that the packed bed reactor and intermittent aeration is efficient in the simultaneous removal of organic matter and nitrogen and is an interesting alternative to be used in the treatment and post treatment of anaerobic reactors.
Keywords: reator biológico; nitrificação; desnitrificação; leito empacotado; espuma de poliuretano e aeração intermitente; biological reactor; nitrification; denitrification; structured bed; polyurethane foam and intermittent aeration; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA